Eksistensi Audit Laporan Dana Kampanye Pada Pemilihan Umum Kepala Daerah di Indonesia - Henry Windrianto Darmoko; Herry Purnomo; Fatchurrahman (Universitas Merdeka Madiun, 2025)
The phenomenon that occurs in Indonesia indicates that the existence of campaign fund report audits in Indonesia is weak and even doubtful. This study aims to reveal the existence of campaign fund report audits in regional head elections in Indonesia. The truth of the existence of campaign fund report audits in regional head elections will be proven through the disclosure of the existence of the implementation of campaign fund report audits. The concept of existence in this study uses Paul Sartre's Existentialism Philosophy which states that: